DESAIN PASAR PROKLAMASI RENGASDENGKLOK KARAWANG DENGAN PENDEKATAN KONSEP ARSITEKTUR KONTEMPORER - Tigor David Manalu; Purnama Sakhrial Pradini; Yusdianto Haryo Soeroso; Yoga Kharisma Hadi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2021)
The market is part of the social life of the community whose development is adjusted to the customs, norms and behavior of an area or territory. Rengasdengklok Market is one of the markets in Karawang Regency which has been established since the Dutch colonial era and looks increasingly shabby and displaces the functions of roads and sidewalks. The slum, dirty and smelly traditional market has made the public's interest in buying, especially the younger age group, reduced so they prefer the Mall even though its location is far from Rengasdengklok District. Rengasdengklok District has also become one of the historical areas for the independence of the Republic of Indonesia, but it is not well known by Indonesian citizens and the Karawang community, especially the young people themselves, so it is necessary to promote historical tourism in crowded places in Rengasdengklok District. Therefore It is necessary to have a good architectural object in terms of building form such as the concept of contemporary architecture which is characteristic, one of which is to harmonize the relationship between the building and the surrounding environment and also the circulation and grouping of spaces that make activity actors in the Rengasdengklok market comfortable and can also be a means. historical promotion in Rengasdengklok District so that it can attract buyers from young age groups to come and get to know the history of Indonesian Independence